The interaction effects of market orientation and entrepreneurial orientation on export performance: a case of sudanese export firms - Ng, Kim-Soon; Belal, Hawaa; Ali Hasaballah, Abdel Hafiz; Ahmad, Abd Rahman (American Scientific Publishers, 2018)
The study investigated the interaction effects of market orientation and entrepreneurial orientation on export performance of the export firms. Research works in marketing and management field investigating different models of the relationships between market orientation, entrepreneurial orientation, and performance are common. However, research that investigates the interaction between these two variables on export performance in developing countries is rare. By using snowball sampling, the survey questionnaire was distributed to export companies in the state of Khartoum, Sudan. The hypotheses formulated were tested using Structural Equation Modeling (AMOS). It was found that there is no significant effect of the interaction of market orientation and entrepreneurial orientation on export performance. However, the interaction between responsiveness to the marketing intelligence and pro-activeness were found significantly related to commitment to learning. Results also indicated that the interactions between the generation of marketing intelligence with innovativeness, and that between dissemination of marketing intelligence with pro-activeness are both significantly related to open mindedness. There is no mediation effect of learning orientation on the relationship between the interaction of market orientation and entrepreneurial orientation with export performance. However, commitment to learning and open-mindedness were found to have a positive influence on export performance. Implication and limitation of the study were discussed.